The Principle of Proportionality in European Union Law as a Prerequisite for Penalization - Długosz, Joanna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2017)
The paper analysis the principle of proportionality, which is widely applied in the EU legal order and is therefore one of the fundamental principles of the system of the European Union. It is one of the legal principles that govern decision-making processes and common strategic objectives, and which are applicable when establishing European Union legislation and transposing it into national law, including in the area of criminal law, although the current analyses do not often focus on discussing this aspect. Due to its complexity and significance for the processes of establishing and applying the law, the principle of proportionality requires detailed and separate discussion, especially in the context of European criminal law.